INOVASI PEMBELAJARAN KOLABORATIF: PENERAPAN SERVICE LEARNING DALAM PENGUATAN BAHASA ASING DI LEMBAGA PENDIDIKAN DESA PLAKPAK PENGANTENAN PAMEKASAN - Kirom, Abdul; Hasan, Zainul (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2024)
Limited foreign language skills among students at educational institutions in Plakpak Village, Pegantenan District, Pamekasan Regency remain a significant challenge in facing the demands of globalization and the world of work. The lack of speaking practice and contextual learning methods has resulted in foreign language learning that is ineffective and meaningless. Based on these issues, this community service activity aims to implement service learning as a collaborative learning innovation that can integrate theory and practice in a social context. The community service method was carried out through a service learning approach with the following stages: (1) identification of foreign language needs in the target educational institution, (2) intensive training based on communicative practice and community service projects, (3) assistance in the implementation of collaborative learning between students and teachers, and (4) evaluation of the improvement in students' foreign language skills. This activity involved teachers, students, and university students as active partners in learning, thereby creating a reciprocal process between the academic world and community needs. The results of the community service showed an increase in learning motivation and basic foreign language communication skills among students. In addition, teachers gained new experiences in applying a service learning approach oriented towards experiential learning. This activity also strengthened the collaborative network between universities and village educational institutions in creating innovative, participatory, and sustainable learning models.